Prognostic factors for outcomes of surgical mobilisation in patients with posttraumatic limited range of motion of the proximal interphalangeal joint: a multivariate analysis. Issue 3 (1st June 2022) - Fujihara, Yuki; Ota, Hideyuki; Watanabe, Kentaro
Abstract: This study aimed to identify the prognostic factors for outcomes of surgical mobilisation in patients with posttraumatic limited range of motion (ROM) of the proximal interphalangeal (PIP) joint and determine which procedure actually improves the PIP joint ROM. A total of 71 fingers (57 patients: 49 men, 8 women; mean age, 41 years) with posttraumatic limited passive ROM of the PIP joint (<60°) who underwent surgical mobilisation were reviewed. Possible prognostic factors, including age, injury type, injured finger, injury in the adjacent finger, and procedure types, were assessed. We defined the PIP joint ROM improvement as the primary outcome in the linear regression analysis. To evaluate surgical efficacy, we classified the surgical treatment options into four categories (volar release, dorsal release, volar and dorsal release, and joint distraction with an external fixator) and compared their outcomes. The mean postoperative improvement in the PIP joint ROM was 12°. In the linear regression analysis, advanced age (estimate, −0.41; 95% confidence interval [CI], −0.76 to −0.06), open injury (estimate, −13.54; 95% CI −27.02 to −0.06), and skin defects (estimate, −23.22; 95% CI −34.83 to −11.61) were associated with worse outcomes; however, the volar approach was associated with favourable outcomes. Surgical mobilisation is strongly recommended when limited ROM of the PIP joint is caused by flexion site contracture. To improve the final outcome of fingers with complex injuries, a tailored treatment strategy is required to avoid dorsal release.